Beneficial use of marine dredged materials as a fine aggregate in ready-mixed concrete: Turkey example - Ozer-Erdogan, Pembe; Basar, H. Merve; Erden, Ibrahim; Tolun, Leyla (ELSEVIER SCI LTD, 2016)
This study describes the potential beneficial use of untreated and treated marine dredged material (DM) in ready-mix concrete (RMC) as a fine aggregate. DMs collected from four Turkish ports/harbours were characterized, assessed according to the National Legislation and transformed into one composite DM. Silica sand was replaced with untreated- and treated-composite-DM (COMP-U/COMP-T) at five ratios (0%, 25%, 50%, 75%, 100%), respectively. Mechanical, durability, leaching, mineralogical/micro-structural properties of DM-based-RMCs were analysed. Concretes having 50% COMP-U and 100% COMP-T met the minimum requirement for C25/30 class RMC. Marine DM can be beneficially used in RMC production; however, DM pre-treatment should be applied. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Beneficial use; Dredged material; Fine aggregate; Ready-mixed concrete; MECHANICAL-PROPERTIES; COARSE AGGREGATE; SEDIMENTS; SAND; STRENGTH; RESTORATION; PERFORMANCE; MANAGEMENT; RESOURCE; CREATION; Construction & Building Technology; Engineering; Materials Science